The Importance of~the 1520 mm~Gauge Rail Transport System for Trans‑Eurasian International Trade in~the Exchange of~Goods - Jakub Doński-Lesiuk (Comparative Economic Research. Central and Eastern Europe, 2022)
The article presents the importance of a specific rail transport system in the logistics service of cargo transported between two generators of international trade in goods - China and the European Union. Using selected operational data relating to the railway systems of several countries (including Belarus, Kazakhstan, Latvia, Russia, and Ukraine), it indicates the great economic importance of the 1520 Space - an area dominated by broad-gauge infrastructure. Beyond the comparative aspect, and against the background of the influence and importance of railways for the economy, it presents the scope and costs of investments that are necessary and desirable to ensure the efficiency and optimization of goods flows. The study covers the growing share of Trans-Eurasian container transport in the volume of cargo handled using the 1520 Space rail infrastructure, which is a key link in Trans-Eurasian supply chains and of which the Russian railway system is an essential component.
Keywords: N70; O57; R41; 330; Trans-Eurasian rail transport of goods; international railways exchange; 1520 Space; transport infrastructure